SHADOW BANKING IN RUSSIA: FACTORS OF PROPAGATION, POSSIBILITIES OF REGULATION - M. A. Abramova; M. V. Mamuta (Финансы: теория и практика)
The article describes the specifics of the development in Russia of parallel or alternative banking, referred to as «Shadow Banking» in the world practice. Particular attention is paid to the factors ensuring its propagation, risks to the economy, regulation methods aimed at risk mitigation including administrative (administrative prohibitive) and economic (financial and regulatory) methods.